2017
DOI: 10.3390/ma10020185
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Static Compression and Low-Velocity Impact Behavior of Tri-Axial Bio-Composite Structural Panels Using a Spherical Head

Abstract: This paper presents experimental results of both quasi-static compression and low-velocity impact behavior for tri-axial bio-composite structural panels using a spherical load head. Panels were made having different core and face configurations. The results showed that panels made having either carbon fiber fabric composite faces or a foam-filled core had significantly improved impact and compressive performance over panels without either. Different localized impact responses were observed based on the locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Matrix compressive failure mode (σ 22 +σ 33 )<0 (4) Here σ ij is the stress component referred to the principal axes x 1 x 2 x 3 , X T , X C , Y T , Y C , represent, respectively, the tension and compression strength along and perpendicular to the fibre direction which is along the x 1 -axis. The shear strength in either the x 1 x 2 -plane or the x 1 x 3 -plane is denoted by S, the S 23 represents the shear strength in the x 2 x 3 -plane.…”
Section: Fibre Tensile Failure Mode σ 11 >0mentioning
confidence: 99%
See 2 more Smart Citations
“…Matrix compressive failure mode (σ 22 +σ 33 )<0 (4) Here σ ij is the stress component referred to the principal axes x 1 x 2 x 3 , X T , X C , Y T , Y C , represent, respectively, the tension and compression strength along and perpendicular to the fibre direction which is along the x 1 -axis. The shear strength in either the x 1 x 2 -plane or the x 1 x 3 -plane is denoted by S, the S 23 represents the shear strength in the x 2 x 3 -plane.…”
Section: Fibre Tensile Failure Mode σ 11 >0mentioning
confidence: 99%
“…After the satisfaction of the damage initiation criterion, the interface stiffness is gradually degraded by a scalar damage variable D. The stress components are expressed by a function of the damage variable as (6) tensile and compressive failure and matrix tensile and compressive failure [9]. The proposed viewpoint is that the damage initiates when one of the four indices ( 1,2,3,4) f    just exceeds 1.0. After damage initiation, a stiffness degradation rule can be used to access the progressive damage behaviour of composite laminates.…”
Section: Damage Model For Interlaminar Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Damage mechanism and failure modes were characterized and results indicated that failure mechanism was expressively affected by stacking sequence of fibers as well as fibres type. Jinghao Li et al [3] conducted experimentation on both quasi-static and low velocity impact for investigation of impact behavior of tri-axial bio-composite structural panels. The core of panels made with foam and face sheets are made with carbon fibers.…”
Section: Introductionmentioning
confidence: 99%